Understanding the Experience of House Arrest with Electronic Monitoring: An Analysis of Quantitative and Qualitative Data - Gainey, Randy R. (International journal of offender therapy and comparative criminology, 2000)
In this article, the authors use both qualitative and quantitative methods to investigate the experiences of offenders on house arrest with electronic monitoring. The data suggest that offenders, for the most part, do not view house arrest with electronic monitoring as particularly problematic, and most cite positive aspects of their program in comparison to jail. However, some aspects of the sanction are seen as more punitive than others, and there is important variation in how punitive offenders view the sanction. With few exceptions, however, offenders'perceptions were not strongly correlated with social and demographic characteristics. The findings are discussed in terms of their implications for criminal justice policy regarding this alternative sanction